Using Bible Commentaries in the Classroom. (2nd January 2013) - Phillips, Gary; Patte, Daniel; Kittredge, Cynthia; Yang, Seung Ai; Ngwa, Kenneth
Abstract: This discussion of the goals and methods of teaching biblical literature is an edited transcription of a panel recorded at the 2010 Society for Biblical Literature conference. The panelists were asked to reflect on William Placher's recently published theological commentary on Mark as an example or test case of how one might use a biblical commentary as a classroom resource. Karl Barth wrote that insofar as their usefulness to pastors goes, most modern commentaries are "no commentary at all, but merely the first step toward a commentary." What value might commentaries have for our students, whether future pastors or undergraduates in the liberal arts? While the panel consisted of teachers of undergraduates as well as theological students, the emphasis of the presentations and subsequent discussion focused mostly on theological formation.